2017
DOI: 10.1103/physreva.95.053849
|View full text |Cite
|
Sign up to set email alerts
|

Observation of spatial quantum correlations in the macroscopic regime

Abstract: Spatial quantum correlations in the transverse degree of freedom promise to enhance optical resolution, image detection, and quantum communications through parallel quantum information encoding. In particular, the ability to observe these spatial quantum correlations in a single shot will enable such enhancements in applications that require real time imaging, such as particle tracking and in-situ imaging of atomic systems. Here, we report on measurements in the far-field that show spatial quantum correlations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Very recently Ma et al [17] reported such squeezing down to frequencies below 700 Hz. In the context of imaging, Kumar et al [27] performed intensity-differencing on an EM-CCD camera using a 4WM source similar to ours and were able to obtain a subtraction noise level 2 dB below shot noise. In those experiments two frames are taken in rapid succession for each of the twin images and are subtracted.…”
Section: Introductionmentioning
confidence: 78%
“…Very recently Ma et al [17] reported such squeezing down to frequencies below 700 Hz. In the context of imaging, Kumar et al [27] performed intensity-differencing on an EM-CCD camera using a 4WM source similar to ours and were able to obtain a subtraction noise level 2 dB below shot noise. In those experiments two frames are taken in rapid succession for each of the twin images and are subtracted.…”
Section: Introductionmentioning
confidence: 78%
“…The defining feature of the EMCCD—the amplification of small numbers of photoelectrons above electronic noise—maintains the linear relationship between signal level and the incident photon flux. Accurate characterization of the amplification process and the conversion to digital units are necessary for comparing intensity levels among pixels 10 , 11 , such as when fitting point-spread functions for super-resolution localization microscopy 2 or when comparing intensity differences across regions of the sensor for quantum correlation detection 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The defining feature of the EMCCD-the amplification of small numbers of photoelectrons above electronic noise-maintains the linear relationship between signal level and the incident photon flux. Accurate characterization of the amplification process and the conversion to digital units is necessary for comparing intensity levels among pixels 10,11 , such as when fitting point-spread functions for super-resolution localization microscopy 2 or when comparing intensity differences across regions of the sensor for quantum correlation detection 12,13 .…”
Section: Introductionmentioning
confidence: 99%